2021
DOI: 10.1002/fuce.202000185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preparation Parameters on the Catalytic Performance of Solid Acid Catalyst SO42−/ZrO2‐CeO2 in Biodiesel Production▴

Abstract: A new solid acid catalyst SO42−/ZrO2‐CeO2 (SZC) was prepared by co‐precipitation method and used in biodiesel production. Different from considering several parameters in available literatures, the effect of all 10 parameters in the preparation process on the catalytic activities of SZC were studied systematically and comprehensively. The catalytic performance was tested by the conversion of Jatropha oil fatty acids (CFA) in esterification. TG, XRD, BET, TEM, NH3‐TPD, FTIR were used to characterize the catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Sulfated zirconia (SZ) is well established as a robust and efficient solid acid catalyst for a variety of reactions of high industrial importance, such as hydrocarbon isomerization, methanol conversion to hydrocarbons, alkylation, acylation, esterification, dehydration, and Fischer–Tropsch processes. 1 4 More recently, sulfated zirconia has also emerged as a promising catalyst for several biorefinery processes, such as esterification, biodiesel preparation, 5 10 furfural synthesis 11 16 and conversion, 17 20 condensation of ketones, 21 glycerol utilization, 22 24 and, conversion of CO 2 to light olefins. 25 Among the biorefinery processes, the upgrading of biomass derived volatile fatty acids (C 3 –C 6 ) to corresponding ketones (ketonization reactions) is a promising strategy for the synthesis of biofuels.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfated zirconia (SZ) is well established as a robust and efficient solid acid catalyst for a variety of reactions of high industrial importance, such as hydrocarbon isomerization, methanol conversion to hydrocarbons, alkylation, acylation, esterification, dehydration, and Fischer–Tropsch processes. 1 4 More recently, sulfated zirconia has also emerged as a promising catalyst for several biorefinery processes, such as esterification, biodiesel preparation, 5 10 furfural synthesis 11 16 and conversion, 17 20 condensation of ketones, 21 glycerol utilization, 22 24 and, conversion of CO 2 to light olefins. 25 Among the biorefinery processes, the upgrading of biomass derived volatile fatty acids (C 3 –C 6 ) to corresponding ketones (ketonization reactions) is a promising strategy for the synthesis of biofuels.…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that the optimal conditions for this catalyst were as follows: a CeO 2 loading of 5%, an ammonia concentration of 14.8 M, a pH value of 8.6, an aging temperature of 293 K, an aging time of 24 h, an impregnation concentration of 0.5 M, an impregnation time of 1 h, a calcination temperature of 773 K, a calcination time of 3 h, and drying prior to calcination. 15 The calcination temperature effect on the catalytic performance of egg shells-derived CaO in biodiesel production has been investigated. The raw materials (chicken and duck eggs) have been calcined at 800, 900, and 1000 C for 1 h. Results showed that for both raw materials, the CaO obtained at 800 C had the best catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The calcination time and temperature (2–6 h and 573–973 K), the aging time and temperature (3–720 h and 268–308 K), the impregnation time and concentration (0.5–4 h and 0.2–2 mol L −1 ), loading amount of CeO 2 (0%–20%), ammonia concentration (0.2–4.8 mol L −1 ), pH value (7.6–9.6), and drying before calcination (yes or no) were the studied parameters. The findings indicated that the optimal conditions for this catalyst were as follows: a CeO 2 loading of 5%, an ammonia concentration of 14.8 M, a pH value of 8.6, an aging temperature of 293 K, an aging time of 24 h, an impregnation concentration of 0.5 M, an impregnation time of 1 h, a calcination temperature of 773 K, a calcination time of 3 h, and drying prior to calcination 15 . The calcination temperature effect on the catalytic performance of egg shells‐derived CaO in biodiesel production has been investigated.…”
Section: Introductionmentioning
confidence: 99%